ANALISIS DAMPAK SHOCK PERTUMBUHAN EKONOMI MITRA DAGANG UTAMA TERHADAP PERTUMBUHAN EKONOMI DAN KETERBUKAAN PERDAGANGAN INDONESIA - Purwanto, Muhammad Rizqy; Rachmad Kresna Sakti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to analyze the response of Indonesia's economic growth and Indonesia's trade openness with each trading partner to economic growth shocks in Indonesia's main trading partners. This study uses a quantitative approach with the VAR / VECM method by analyzing the impulse response between variables, using time-series data. The sample used in this study amounted to 378 annual data from 1981-2022 sourced from the World Bank and IMF. The results obtained from the response test show that there is a positive response from Indonesia's economic growth to shocks to US economic growth, and a negative response from Indonesia's trade openness with the United States. There is a positive response from Indonesia's economic growth to China's economic growth shocks, and a negative response from Indonesia's trade openness with China. There is a positive response of Indonesia's economic growth and trade openness with Japan to Japan's economic growth shocks. There is a negative response from Indonesia's economic growth and trade openness with Malaysia to shocks in Indonesia's economic growth with Malaysia.